Prognostic value of volumetric PET parameters in unresectable and metastatic esophageal cancer. Issue 3 (March 2016) - Tamandl, Dietmar; Ta, Julie; Schmid, Rainer; Preusser, Matthias; Paireder, Matthias; Schoppmann, Sebastian F.; Haug, Alexander; Ba-Ssalamah, Ahmed
Abstract: Purpose: To assess the prognostic value of volumetric parameters measured with PET/CT in patients with advanced or metastatic esophageal cancer (EC). Materials and methods: We identified 71 patients (33 adenocarcinoma [AC] and 38 squamous cell carcinoma [ESCC]) with unresectable or metastatic EC who had PET/CT prior to palliative treatment. Volumetric parameters (metabolic tumor volume [MTV], total lesion glycolysis [TLG], tumor length [TL]) as well as maximum and mean standardized uptake (SUVmax, SUVmean) were obtained from 18 F-FDG PET/CT studies. The correlation between overall survival (OS) and established clinical parameters was assessed using a Cox proportional hazards model. Results: ESCC patients had higher SUVmax and SUVmean compared to AC ( p = 0.002 and p < 0.001, respectively). There was an association of lower SUVmax and SUVmean with metastatic compared to locally advanced tumors (e.g., median SUVmax stage IV: 14.9, 95% confidence interval [95% CI 4.4–35.5] vs. stage IIIA-C: 23.3 [9.2–40.6], p = 0.017). TL, MTV and TLG showed an association to OS for all patients and for the subgroup of AC patients (AC; TL: Hazard ratio [HR] 3.23, [95% CI 1.03–10.11], p = 0.044; MTV: HR 3.16, [95% CI 1.08-9.23], p = 0.035). There was no correlation between PET parameters and survival in ESCC patients. Clinical nodal status was the only clinical variable associated to OS (HR 2.45 [95% CI 1.26–4.75], p = 0.008) in AC patients. In a multivariate analysis, nodal status and MTV remained as independent factors associated to OS (N: HR 9.98, [95% CI 1.28–78.11], p = 0.028; MTV: HR 1.02, [95% CI 1.01–1.03], p = 0.003). Conclusions: MTV predicted poor OS in patients with advanced AC. No PET parameters were associated to OS in ESCC patients.